Klinik Laboratuvarda Gereksiz Testleri Önleme Yöntemi. - GÖNEL, Ataman; KOYUNCU, İsmail; BAYRAKTAR, Nihayet; ÇAĞLAYAN, Murat (Journal of Harran University Medical Faculty / Harran Üniversitesi Tıp Fakültesi Dergisi, 2022)
Background: In countries where health services are free, laboratory test costs are increasing. New software methods for preventing unnecessary tests without obstructing the test orders can provide significant savings. The aim of this study was to detect unnecessary test amounts that were prevented for 2 years with algorithms defined in intelligent laboratory software. Materials and Methods: AlinIQ (Abbott, USA) software has been defined algorithms that detect and cancel unnecessary tests without preventing clinicians from ordering. The prevented quantities of five different laboratory tests (direct bilirubin, chlorine, AST, fPSA and fT3), which were requested from January 2018 to January 2020, were calculated. It was compared with the proportional amo- unts of the same tests that were performed between January 2016 and January 2018, which were studied without software. Results: Algorithms prevented 261540 AST, 174096 direct bilirubin, 135373 chlorine, 27486 FT3, 1160 free PSA. A total of 599656 tests were saved in 2 years. Conclusions: In this study, defined algorithms successfully prevented unnecessary tests. Any clinical laboratory can use these simple algorithms and adapt it for other tests. Millions of dollars can be saved by using intelligent laboratory software in clinical laboratories.